2013
DOI: 10.1016/j.jallcom.2012.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman study on phase transitions in 0.24Pb(In1/2Nb1/2)O3–0.43Pb(Mg1/3Nb2/3)O3–0.33PbTiO3 single crystal

Abstract: Polarized Raman spectroscopy was performed to investigate the local lattice structure and phase transitions of unpoled 0.24Pb(In1/2Nb1/2)O3–0.43Pb(Mg1/3Nb2/3)O3–0.33PbTiO3 (0.24PIN–0.43PMN–0.33PT) single crystal in the temperature range from 30 °C to 260 °C. MA- and MC-type monoclinic phases were detected by micro-Raman spectra measured in different micro areas. Temperature dependence of Raman intensities, frequency shifts, mode merge and intensity ratios in the VV and VH geometries were investigated. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the change of frequency, sharpness, and intensity of the peaks are connected with the local random fields and phase transitions. In previous reports, some researchers found that the evolution of intensity ratio false(I270normalcm1false)/false(I790normalcm1false) with temperature could indicate the structural transformations in PMN‐PT and PIN‐PMN‐PT systems . The peaks of 270 and 790 cm − 1 correspond to the phonon modes of E(LO2) and A1(LO3), respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the change of frequency, sharpness, and intensity of the peaks are connected with the local random fields and phase transitions. In previous reports, some researchers found that the evolution of intensity ratio false(I270normalcm1false)/false(I790normalcm1false) with temperature could indicate the structural transformations in PMN‐PT and PIN‐PMN‐PT systems . The peaks of 270 and 790 cm − 1 correspond to the phonon modes of E(LO2) and A1(LO3), respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The temperature dependent depolarization ρ value of the vibrational modes around 71, 100, and 803 cm –1 in Figure d fluctuates first at 293–343 K corresponding to the instable monoclinic phase. The depolarization fluctuation near room temperature illustrates the unstable lattice polarizability, which would be attributed to the monoclinic symmetry with unstable phase coexistence. An abrupt increase near 400 K confirms the phase transition ( T M – T ) from monoclinic to T phase.…”
Section: Resultsmentioning
confidence: 99%
“…Phase instability and transverse phonon localization are the main causes for the emergence of metastable monoclinic (M) phase bridging rhombohedral (R) and tetragonal (T) symmetries. , Intermediate M-symmetry (M a , M b , and M c ) groups are believed to balance the accommodated strain and favor the multidirectional polarization states at MPB. , The as-grown PMN-based relaxor ferroelectric crystal has a rhombohedral-like (R-like) M a (space group Cm ) and tetragonal-like (T-like) M c (space group Pm ) phases coexisting at room temperature, presenting an adjacent laminar domain structure. ,− It should be noted that exploring Pb-based ferroelectric performances requires consideration of the synergistic contributions from the lattice symmetry, polar order, and internal energy. Therefore, it is necessary to explore the spatial relationships between the structure, internal energy, and polarization disorder in Pb-based relaxor ferroelectrics with MPB composition, and to further strengthen the understanding of the structure-related piezoelectric contributions.…”
Section: Introductionmentioning
confidence: 99%
“…It is showed that the Raman scattering around 50, 140, 340, 380, and 825 cm −1 was very sensitive to the structural transformation of Pb‐based relaxor ferroelectrics 5,21–23 . Since Raman mode broadening, merging, and frequency shift are related to the ferroelectric phase transition of relaxor‐based ferroelectric perovskites, 22,23 the intensity and peak shape of the Raman spectrum depend to a large extent on the crystal orientation and polarization configuration 24 . Figure 3B shows the variation of Raman peak position with various temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref. [ 24 ]. Modeling approaches used in the above work generally involved modeling the flow of a high viscosity resin through porous media and modeling the chemical reactions and volumetric changes during processing.…”
mentioning
confidence: 99%